Lithologic Structure of the Anninghe Fault Zone: Constraints From High-Pressure Wave Velocity Experiments - Miao, Sheqiang; Zhou, Yongsheng; Ma, Xi; Dang, Jiaxiang (Frontiers in Earth Science, 2022)
The P-wave velocities of typical rocks in the Anninghe fault zone under pressures of 50–600 MPa were systematically measured. The P-wave velocities of the felsic, intermediate, and mafic rock types under atmospheric pressure were 5.86 km/s, 6.06 km/s, and 6.50 km/s, respectively, with pressure coefficients of 2.19 × 10−4 km/s/MPa, 3.80 × 10−4 km/s/MPa, and 4.03 × 10−4 km/s/MPa, respectively. The results were combined with deep-imaging seismic data to establish crustal rock composition models at different depths in the study area. The composition of the Anninghe crust is very different in the horizontal and vertical directions. The most notable feature in the vertical direction is that the lithologic compositional change is gradual rather than abrupt with increasing depth. In the middle and upper crust, shallower than 25 km, the lithologic difference between the southern and northern sections of the Anninghe fault zone is primarily that the rocks in the southern section (Xichang) are more felsic than those in the northern section (Shimian).